Periodontal health outcomes after early versus delayed orthodontic treatment following periodontal surgery: a randomized controlled trial - Rekha Sharma; Anunay Gupta; Vinni Arora; Shikha Tewari; Davender Kumar (Clinical and Investigative Orthodontics)
Objective To evaluate the effect of early versus delayed start of orthodontic treatment after periodontal surgery on periodontal parameters in periodontally compromised patients.Trial Design Two-arm parallel group, single-centre, randomized controlled trialMaterial and Methods Thirty-six patients (8 males and 28 females, mean age 30.9 yrs ± 5.49) with periodontally compromised dentition needing orthodontic intervention underwent open flap debridement in maxillary and mandibular anterior teeth and were then block randomized to either early (10 days after periodontal surgery) or delayed (3 months after periodontal surgery) orthodontic treatment groups. Clinical parameters (CAL, PPD, PI, GI and BOP) were recorded at T0 (Baseline records before any intervention), T1 (3-month post-periodontal surgery) and T2 (1 year after the start of orthodontic treatment) radiological parameters (ABL) were analysed at T0 and T2 using CBCT radiographs. Treatment duration of various orthodontic stages was also evaluated and compared for both the groups.Results All 36 patients completed the trial. Both groups showed a significant improvement in all periodontal parameters with no statistically significant difference between them at the end of the study period (T0–T2). In the early start group, total treatment time (TTOT) was significantly reduced in comparison to the delayed start group (10.57 months versus 14.05 months). No adverse event or harm was recorded.Conclusion Orthodontic treatment can be started as early as 10 days after periodontal surgery with no detrimental effect on the periodontium with the added advantage of a reduced overall treatment time.